Informacja Bieżąca . no. 6, 1981 - Uniwersytet Warszawski NSZZ "Solidarność" Region Mazowsze, [ed. Andrzej Krawczyk, Jerzy Wocial] (NSZZ "Solidarność" UW, 1981)
Creation and circulation: For internal use